Controle do processo da irrigação no sistema de aspersão convencional em Palotina-PR - Frigo, Jiam Pires (2012)
Sprinkler irrigation, an artificial method of water application, supplies the whole or part of water that crops need. It can be used in several crops. Besides, it is easily adapted to different soils and topographies. Irrigation should be carried out according to the right bulk and uniformity, since it is an important factor to be considered when irrigation systems are under evaluation. Most losses are associated to a direct evaporation and wind drift of water. Thus, this study aimed at evaluating daytime and nighttime irrigation of a conventional sprinkler system, using the Christiansen Uniformity Coefficient (CUC) and quality control techniques. It was carried out at Adroaldo Augusto Colombo, a State Agricultural School in Palotina, Paraná. At the irrigation period, four Xcel-wobbler sprinklers were used, with an anti-drift system during day and nighttime. The weather parameters were recorded during the essays with an anemometer and thermo-hygrometer and both were digital and portable. The Christiansen Uniformity Coefficient was correlated with the process capability index ( ), and by Shewhart control charts, it was observed that irrigation was under control over time. In sprinkler irrigation, the best performance of the system was registered during the night period. At last, this trial concluded that in Palotina, PR, from July to September, the best period for sprinkler irrigation was up from four o clock P.M.